On the development of Arabic three-digit number processing in primary school children - Mann, Anne; Moeller, Korbinian; Pixner, Silvia; Kaufmann, Liane; Nuerk, Hans-Christoph (Journal of Experimental Child Psychology, 2012)
Abstract: The development of two-digit number processing in children, and in particular the influence of place-value understanding, has recently received increasing research interest. However, place-value influences leading to decomposed processing have not yet been investigated for multi-digit numbers beyond the two-digit number range in children. Therefore, we evaluated the separate influences of hundreds, tens, and units on three-digit number processing by means of the hundred distance effect, the decade-hundred compatibility effect, and the unit-hundred compatibility effect in a longitudinal design from Grade 2 to Grade 4. In a number magnitude comparison task, a strong hundred distance effect indicated that the magnitudes of the hundreds digits were predominantly processed. We also observed indexes of decomposed parallel processing of hundreds and units digits but not of hundreds and tens digits. Regarding the developmental trajectories, the hundred distance effect and the unit-hundred compatibility effect showed a reliable trend to increase with grade level. However, both the significance and the increase with grade level of decomposed parallel processing were observed to be less consistent than expected. The latter is discussed in terms of different processing strategies as well as specificities differentiating between two- and three-digit numbers. Taken together, these are the first data showing decomposed processing of three-digit numbers in children. Yet, it must be noted that the results also indicate that findings from two-digit number processing cannot simply be generalized to the three-digit number range.